2016
DOI: 10.1021/acs.iecr.6b01816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Biopolymer Charge and the Nanoclay Morphology on Nanocomposite Materials

Abstract: This work represents a contribution to the design, preparation and characterization of nanocomposite materials based on biocompatible components. The effect of composition, filler geometry and polymer charge were highlighted and their role on the final properties of the nanocomposites was revealed. We combined some biopolymers (methylcellulose, alginate, chitosan) with two nanoclays (kaolinite sheets and halloysite nanotubes) to prepare nanocomposites by means of the casting method from water. The thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 60 publications
(117 reference statements)
4
69
0
Order By: Relevance
“…From Figures 6-11, it can be observed that when the value of effective tensile strain ε e is low, the PNCs behave as linearly elastic solids until the effective tensile strain ε e is close to the yield strain of the polymeric matrix. The effective elastic moduli E e extracted from the present numerical experiments (see Figure 4) are close to those available in the literature [11,12]. In addition, it can also be found from Figures 6-11 that the PNCs exhibit slightly softening behavior prior to the arrival of the yield strain of the polymeric matrix.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…From Figures 6-11, it can be observed that when the value of effective tensile strain ε e is low, the PNCs behave as linearly elastic solids until the effective tensile strain ε e is close to the yield strain of the polymeric matrix. The effective elastic moduli E e extracted from the present numerical experiments (see Figure 4) are close to those available in the literature [11,12]. In addition, it can also be found from Figures 6-11 that the PNCs exhibit slightly softening behavior prior to the arrival of the yield strain of the polymeric matrix.…”
Section: Resultssupporting
confidence: 85%
“…Among those, the most recent research investigated the effects of nanoclay morphologies (e.g., particle length, aspect ratio, bird nest structure, aggregation, etc. of halloysite and kaolinite nanoclay particles) on the thermal stability, surface wettability, and mechanical properties of biopolymer nanocomposite films for food packaging and other applications [11,12]. The studies showed that the thermal, tensile and surface wetting properties of the pectin resin can be noticeably improved by exfoliated halloysite nanotubes at relatively high weight concentration, which form unique bird nest structures in the pectin matrix of the resulting bionanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of HNTs shows that the external surface contains siloxane (Si-O-Si) groups, aluminol (Al-OH), and silanol (Si-OH) groups [17,18]. The effect of the biopolymer charge on nanocomposite materials was thoroughly discussed in [19]. HNTs possess a much better dispersion property and potential ability for the formation of hydrogen bonding [20] than other natural silicates such as montmorillonite and kaolinite.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Moreover, they have biocompatibility [15] and show no toxicity in vivo [16] and in vitro [17]. These characteristics make HNTs excellent smart materials for the most diverse applications-for example: food packaging [18][19][20], drug delivery [21][22][23][24][25][26], environment remediation and wastewater treatment [27], cultural heritage [28][29][30][31][32], and additives for enhancing the performances of polymers [14,33].…”
Section: Introductionmentioning
confidence: 99%